Overexpression of an Arabidopsis thaliana galactinol synthase gene improves drought tolerance in transgenic rice and increased grain yield in the field. Issue 11 (3rd May 2017) - Selvaraj, Michael Gomez; Ishizaki, Takuma; Valencia, Milton; Ogawa, Satoshi; Dedicova, Beata; Ogata, Takuya; Yoshiwara, Kyouko; Maruyama, Kyonoshin; Kusano, Miyako; Saito, Kazuki; Takahashi, Fuminori; Shinozaki, Kazuo; et al.
Abstract: Drought stress has often caused significant decreases in crop production which could be associated with global warming. Enhancing drought tolerance without a grain yield penalty has been a great challenge in crop improvement. Here, we report the Arabidopsis thaliana galactinol synthase 2 gene ( AtGolS2 ) was able to confer drought tolerance and increase grain yield in two different rice ( Oryza sativa ) genotypes under dry field conditions. The developed transgenic lines expressing AtGolS2 under the control of the constitutive maize ubiquitin promoter ( Ubi:AtGolS2 ) also had higher levels of galactinol than the non‐transgenic control. The increased grain yield of the transgenic rice under drought conditions was related to a higher number of panicles, grain fertility and biomass. Extensive confined field trials using Ubi:AtGolS2 transgenic lines in Curinga, tropical japonica and NERICA4, interspecific hybrid across two different seasons and environments revealed the verified lines have the proven field drought tolerance of the Ubi: AtGolS2 transgenic rice. The amended drought tolerance was associated with higher relative water content of leaves, higher photosynthesis activity, lesser reduction in plant growth and faster recovering ability. Collectively, our results provide strong evidence that AtGolS2 is a useful biotechnological tool to reduce grain yield losses in rice beyond genetic differences under field drought stress.